2020
DOI: 10.30699/ijp.2020.104017.2052
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Benign Brenner Tumor with Mucinous Cystadenoma in an Ovarian Mass

Abstract: Scan to discover online Ovarian cancer is the most lethal gynecologic malignancy. The surface epithelial tumor is the most common type of ovarian cancer. Among these, the mucinous tumors account for 10-15% of ovarian tumors. Mucinous ovarian tumors are among the most difficult ovarian neoplasms for surgical pathologists to interpret. Mucinous tumors sometimes coexist with other surface epithelial tumors. Therefore, making the accurate diagnosis of the mucinous tumors is essential. On the other hand, associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Other smaller studies reported a higher percentage of association reaching up to 30% [ 21 , 39 ]. This higher percentage may be attributed to small areas of mucinous metaplasia commonly found in BTs that might be clinically insignificant [ 40 ]. In our study, we report an associated ipsilateral mucinous cystadenoma in 11% of cases, increasing to 22%, when accounting for contralateral tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other smaller studies reported a higher percentage of association reaching up to 30% [ 21 , 39 ]. This higher percentage may be attributed to small areas of mucinous metaplasia commonly found in BTs that might be clinically insignificant [ 40 ]. In our study, we report an associated ipsilateral mucinous cystadenoma in 11% of cases, increasing to 22%, when accounting for contralateral tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, they can be easily missed due to inadequate sampling. Mucinous tumors and BTs tend to be negative for PAX-2 and PAX-8, two highly sensitive mullerian epithelial markers that are often positive in other ovarian epithelial neoplasms [ 40 , 41 ]. This further suggests shared histogenesis of these two lesions [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no side preference and the masses had involved right or left ovaries equally. All the patients underwent TAH-BSO for treatment because of menopausal status and possibility of malignancy [4] , [8] , [9] , [10] , [11] , [12] .…”
Section: Discussionmentioning
confidence: 99%
“…When most well-differentiated tumors are observed, the possibility of metastatic tumors is often ignored (Zhu et al, 2020). A study found that 70% of cases initially diagnosed as primary tumors can be reclassified as metastatic mucinous cancer with extraovarian diseases (Nazari and Dehghani, 2020). Besides macroscopic and microscopic features, immunohistochemical staining can also be used for differential diagnosis.…”
Section: Introductionmentioning
confidence: 99%